The relationship between foreign exchange reserves, Pula exchange rate and inflation in Botswana - Israel, Bofelo (Department of Finance and Tax, 2023)
This study examines the relationship between foreign exchange reserve, Pula exchange rate and inflation in Botswana over the period 1995-2020. The period covered contains recent data on level of foreign exchange reserves through global events like Covid-19 pandemic in which significant drawdowns in foreign reserves were experienced and not covered in prior studies. Secondary time series data was sourced from Bank of Botswana financial statistics bulletin and a linear regression was run for two models using R studio statistical software. Unit root and correlation tests were run on the data to ensure the variables were stationery and error terms correlation was eliminated in the time series. Regression equation showed that the relationship between foreign exchange reserves and inflation was negative. Similarly, the second regression revealed that the correlation between foreign exchange reserves and foreign exchange rates was negative. Empirical results further revealed that foreign exchange reserves have no statistically significant impact on inflation and exchange rates in Botswana. The statistically insignificant relationship results between the variables implies that foreign exchange reserves have not significantly influenced exchange rate and inflation which may be due to sterilization by the central bank, therefore, other factors may be responsible for changes in exchange rate and inflation locally. This may indicate that the monetary policy framework which requires foreign exchange reserves have served the country well as it maintained a stable exchange rate and did not stir inflation. However, monetary authorities should note that the current framework may not be sustainable given the tremendous pressure that foreign reserved faced in recent years and a move to a floating exchange regime should be considered as a long-term policy goal. The negative correlation of foreign reserves with inflation and exchange rate further suggest to the monetary authorities that Botswana's economy may be influenced by endogenous monetary policies rather than external variables. The relationship between exchange rates and foreign reserves is consistent with elasticity approach and economic theory of modern mercantilism which predict a negative relationship between the two variables. This may provide monetary authorities and policy makers with a framework that explains the link of Botswana's foreign reserves and exchange rates.